How superoxide reductases and flavodiiron proteins combat oxidative stress in anaerobes - Martins, Maria C.; Romão, Célia V.; Folgosa, Filipe; Borges, Patrícia T.; Frazão, Carlos; Teixeira, Miguel (Free radical biology & medicine, 2019)
Microbial anaerobes are exposed in the natural environment and in their hosts, even if transiently, to fluctuating concentrations of oxygen and its derived reactive species, which pose a considerable threat to their anoxygenic lifestyle. To counteract these stressful conditions, they contain a multifaceted array of detoxifying systems that, in conjugation with cellular repairing mechanisms and in close crosstalk with metal homeostasis, allow them to survive in the presence of O2 and reactive oxygen species. Some of these systems are shared with aerobes, but two families of enzymes emerged more recently that, although not restricted to anaerobes, are predominant in anaerobic microbes. These are the iron-containing superoxide reductases, and the flavodiiron proteins, endowed with O2 and/or NO reductase activities, which are the subject of this Review. A detailed account of their physicochemical, physiological and molecular mechanisms will be presented, highlighting their unique properties in allowing survival of anaerobes in oxidative stress conditions, and comparing their properties with the most well-known detoxifying systems. [Display omitted] •Anaerobes have a plethora of systems to cope with oxidative stress.•Superoxide reductases are alternative iron enzymes for superoxide detoxification.•Flavodiiron enzymes are main oxygen and nitric oxide scavengers, namely in anaerobes.